Design Android Applications My Mind Mapping (M3) Physical Education, Sport, & Health Subject Curriculum 2013 for Teachers Guidance Xth Grade Vocational High School - Wicahyani, Sri; Kasmini Handayani, Oktia Woro; Hartono, Mugiyo (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
The android app on the smartphone makes it easy for a user to communicate and get access to various information. The purpose of this research is to design an android based application in the form of mind mapping. This application is a form of transformation from the manual form (book, e-book, module, etc.) to digital form in the form of an application containing Core Competence & Basic Competence, materials, and learning model for teacher guidance of Physical Education, Sport, & Health Subject Xth grade Vocational High School. This research uses ADDIE model which includes analysis, design, development, implementation, and evaluation. The results of the product trial at first stage curriculum experts with the average score of 3.4 (67%) included the